Extended-release trazodone in the treatment of major depressive disorder - Karamustafalioglu, Oguz; Dilbaz, Nesrin; Caykoylu, Ali; Alkin, Tunc; Gonul, Ali Saffet; Atmaca, Murad (Cumhuriyet Univ Tip Fak Psikiyatri Anabilim Dali, 2019)
Major depressive disorder is a common psychiatric disorder. The aim of the treatment is to improve daily functions with remissions in symptoms, and antidepressants are the first-line treatments for a major depressive episode (moderate-severe depressive episode). In this paper, the pharmacological properties, clinical efficacy and safety of extended-release trazodone (TzCOAD) are studied. Expert opinion: A single daily dose of TzCOAD may provide similar efficacy and increased tolerability to immediate-release trazodone (TzIR) and other antidepressants.
Major depresif bozukluk tedavisinde uzatılmış salımlı trazodon
Keywords: major depressive disorder; extended-release trazodone (single dose of TzCOAD per day); immediate-release trazodone (three doses of TzIR per day)